Indenture, Camden County, 1879 - State of Georgia, Camden County (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1879)
Indenture, Camden County, 1879. Handwritten record in ink on ruled paper. Indenture between F.M. Adams to N.B. Stafford for 10 acres, Crow Harbor tract. Camden County, Georgia. April 8, 1879. 3 pages.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Deeds; Camden County (Ga.); Court Records; Records and correspondence; Trust indentures